2008
DOI: 10.1074/jbc.m805468200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Inhibitor of Protein Phosphatase-1 (NIPP1) Directs Protein Phosphatase-1 (PP1) to Dephosphorylate the U2 Small Nuclear Ribonucleoprotein Particle (snRNP) Component, Spliceosome-associated Protein 155 (Sap155)

Abstract: Pre-mRNA splicing entails reversible phosphorylation of spliceosomal proteins. Recent work has revealed essential roles for Ser/Thr phosphatases, such as protein phosphatase-1 (PP1), in splicing, but how these phosphatases are regulated is largely unknown. We show that nuclear inhibitor of PP1 (NIPP1), a major PP1 interactor in the vertebrate nucleus, recruits PP1 to Sap155 (spliceosome-associated protein 155), an essential component of U2 small nuclear ribonucleoprotein particles, and promotes Sap155 dephosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 40 publications
4
59
0
Order By: Relevance
“…The cell lines expressed the fusions in a doxycycline (Dox)-dependent manner and to a similar extent (Figs S1A and S2A). As expected (Tanuma et al, 2008;Van Dessel et al, 2010), EGFP traps of the NIPP1-Wt and NIPP1-Fm fusions showed an association with endogenous PP1, which was not seen with the NIPP1-Pm and NIPP1-Fm+Pm fusions (Figs S1B and S2B). The associated PP1 was inactive with glycogen phosphorylase as substrate but the phosphatase activity could be revealed by trypsinolysis, which destroys NIPP1 but not PP1 (Beullens et al, 1998), confirming that NIPP1-Wt and NIPP1-Fm inhibit PP1 (Fig.…”
Section: The Overexpression Of Nipp1 Causes An Arrest In Mitosis and mentioning
confidence: 63%
See 3 more Smart Citations
“…The cell lines expressed the fusions in a doxycycline (Dox)-dependent manner and to a similar extent (Figs S1A and S2A). As expected (Tanuma et al, 2008;Van Dessel et al, 2010), EGFP traps of the NIPP1-Wt and NIPP1-Fm fusions showed an association with endogenous PP1, which was not seen with the NIPP1-Pm and NIPP1-Fm+Pm fusions (Figs S1B and S2B). The associated PP1 was inactive with glycogen phosphorylase as substrate but the phosphatase activity could be revealed by trypsinolysis, which destroys NIPP1 but not PP1 (Beullens et al, 1998), confirming that NIPP1-Wt and NIPP1-Fm inhibit PP1 (Fig.…”
Section: The Overexpression Of Nipp1 Causes An Arrest In Mitosis and mentioning
confidence: 63%
“…Full-length NIPP1 binds to PP1 with an extremely high affinity and inhibits the phosphatase towards all tested protein substrates except FHA ligands O'Connell et al, 2012;Tanuma et al, 2008). Given that the mitotic-arrest phenotype induced by the overexpression of NIPP1 was entirely dependent on a functional PP1-binding site, we reasoned that the phenotype could be caused by titrating PP1 away from other PIPs.…”
Section: The Overexpression Of Nipp1 Causes An Arrest In Mitosis and mentioning
confidence: 99%
See 2 more Smart Citations
“…Co-transcriptional dephosphorylation could then promote loading of SF1-U2AF 65 on the emerging pre-mRNA during the early stages of splicing. Accordingly, SF1 associates with U2AF 65 in extra-spliceosomal complexes (6), and phosphorylation and dephosphorylation events such as this one are required for pre-mRNA splicing (e.g., (68)(69)(70)). Indeed, the influences of SPSP phosphorylation on any SF1 functions other than UHM and RNA interactions have yet to be examined.…”
Section: Uhmk1 Phosphorylation Slightly Reduces Sf1-u2afmentioning
confidence: 99%